(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The objective of this research is to examine the acute effects of self-myofascial release through foam roller and static stretching methods on the vertical jump performance of taekwondo players. In this cross-sectional study, a randomized controlled experimental method, one of the quantitative research models, was used. 21 taekwondo players participated in this research voluntarily. The mean age of the participants was 15.95±,865; the mean height was 172.90±3,846 and the mean body weight was 61,86±5,379. On the first day of the study, low-paced jogging was performed for 5 minutes at a heart rate of 120 (RS V800) and then their vertical jump performance was measured. On the second day of the research, low-paced jogging was performed for 5 minutes, and then a static stretching protocol was applied to taekwondo players, and then their vertical jump performance was measured. On the third day of the research, low-paced jogging was performed for 5 minutes and then self-myofascial release through foam roller protocol was applied to taekwondo players and then their vertical jump performances were measured. As a result of the research, it was determined that there was no statistical difference between 5 minutes of jogging at a slow pace and static stretching. However, it was determined that there were statistically significant differences both between 5 minutes of jogging at a slow pace and self-myofascial release and between static stretching and self-myofascial release (p<0.05). In conclusion, it can be said that self-myofascial release through foam roller exercises can affect vertical jump performance positively and at an acute level.